Palladium‐Catalyzed C−H Arylation of α, β‐Unsaturated Imines: Catalyst‐Controlled Synthesis of Enamine and Allylic Amine Derivatives. (5th February 2016) - Li, Minyan; González‐Esguevillas, María; Berritt, Simon; Yang, Xiaodong; Bellomo, Ana; Walsh, Patrick J.
Abstract: A unique chemo‐ and regioselective α‐ and γ‐arylation of palladium azapentadienyl intermediates is presented. Two distinct catalysts and sets of conditions successfully controlled the regioselectivity of the arylation. These methods provide the first umpolung C−H functionalization of azapentadienyl palladium intermediates and enable the divergent synthesis of allylic amine and enamine derivatives, which are of significant interest in the pharmaceutical industry.